Freedom of Expression: "Pornography" in the Digital Age Perspective on Criminal Justice System Synchronization: - - Syamsul Fatoni; Rusmilawati Windari (LEGAL BRIEF, 2026)
The formulation of the problem in this study is that freedom of expression related to pornography in the digital era requires synchronization of the criminal justice system, so the aim of this study is to harmonize its handling. The research method is doctrinal research using primary and secondary legal materials that produce legal arguments, legal theories/legal concepts and tertiary legal materials. Using a statute approach, conceptual approach, comparative approach and deductive analysis. The results of the research, substantial, structural and cultural synchronization are needed in the Criminal Justice System to handle pornography in the digital era. Article 28J paragraph (1,2) of the 1945 Constitution of the Republic of Indonesia, Article 8 of Law No. 44/2008 concerning Pornography, Constitutional Court Decision No. 82/PUU-XVIII/2020, Law No. 19/2016 concerning Amendments to Law No. 11/2008 concerning Electronic Information and Transactions, Article 70 of Law No. 39/1999 concerning Human Rights and Presidential Decree No. Law No. 25/2012, which regulates the prevention and handling of pornography, requires freedom of expression within the law, not absolute freedom. Synergy between the central government, regional governments, the Ministry of Communication and Digital, the Indonesian Broadcasting Commission, religious institutions, the Child Protection Commission, the National Commission on Violence Against Women, the Criminal Justice System, and international cooperation is essential. Therefore, research contributions are needed to realize the synchronization of the Criminal Justice System with efforts to eradicate pornography in the digital era